MORPHOLOGY AND STATISTICAL ANALYSIS OF ORAL MUCOSAL LEUKOPLAKIA (Archive of Conferences, 2021)
Leukoplakia (Greek leucosok, French laque-plate) is the freezing of all areas of the oral mucosa and the red border of the lips as a result of long-term local factors. In addition to frostbite, inflammatory infiltration of the subepithelial layer and sometimes acute epithelial growth to varying degrees are observed. There are three clinical morphological types of leukoplakia